Association between serum calcium levels and first stroke: A community-based nested case-control study - Ding, Congcong; Bi, Chonglei; Lin, Tengfei; Liu, Lishun; Song, Yun; Wang, Binyan; Wang, Ping; Fang, Chongqian; Ma, Hai; Huang, Xiao; Xu, Xiping; Zhang, Hao; et al. (Frontiers in Neurology, 2022)
Background: Evidence from epidemiologic studies has been limited and inconsistent regarding the role of serum calcium in stroke incidence risk. We aimed to evaluate the association between serum albumin-corrected calcium and the risk of first stroke in Chinese community-dwelling population. Methods: The study sample population was drawn from “H-type Hypertension and Stroke Prevention and Control Project”. Using a nested case-control study, a total of 1255 first stroke cases and 1255 controls matched for age, sex and village were included in the final data analysis. We measured the serum calcium by inductively coupled plasma mass spectrometry (ICP-MS) and assessed the associations between serum albumin-corrected calcium and first stroke using conditional logistic regression. Results: The overall mean (SD) serum albumin-corrected calcium was 8.9 (0.6) mg/dL. Compared with the middle tertile (8.7 to 9.1 mg/dL), the multivariate-adjusted ORs (95% CIs) of first total stroke associated with the lowest tertile and the highest tertile of serum albumin-corrected calcium were 1.37 (1.10, 1.70) and 1.30 (1.04, 1.62), respectively. Similar trends were observed for first ischemic stroke. Consistently, restricted cubic spline showed a U-shaped association between serum albumin-corrected calcium and risk of total stroke and ischemic stroke. However, serum albumin-corrected calcium had no significant effect on first hemorrhagic stroke. No significant effect modification was observed in subgroup analysis. Conclusions: Our results suggested a U-shaped association between serum calcium and fist stroke; both low and high serum calcium levels were associated with an increased risk of first stroke in Chinese population.